Human Fingerprint Study from Zaqlul An-Najjar's Perspective with the STIFIn Method: Study of the Meaning of Banan in the Qur'an - Aisyah, Siti; Mahbub, Muhammad Ihsan (QiST: Journal of Quran and Tafseer Studies, 2025)
The era of digitalization with access using fingerprints has very important aspects in various fields. This study aims to describe the relationship between human fingerprints and scientific interpretation from the perspective of Zaghlul an-Najjar and the STIFIn method. This study uses a descriptive qualitative method with a library research approach. The data collection techniques carried out are documentation techniques and literacy techniques. The data analysis used is content analysis. The steps used are to select, compare, combine, and sort various meanings until relevant data is found. The data validation technique used is source triangulation. The result of this study is the correlation of Zaghlul an-najjar's perspective which focuses on the interpretation of 'ilmi with the interpretation of patterns that seek to reveal the relationship between the kauniyah verses in the Qur'an and the field of science to show the truth of the miracles of the Quran. The perspective of Zaghlul an-najjar Fingerprints in Q.S Al-Qiyamah verse 4 is the relevance of miracles developed by modern science in the late 19th or early 20th century. Zaghlul interprets that fingerprints are human identities that will not be the same for each individual and are also under the verse of human creation. Meanwhile, the STIFIn method is an alternative approach to analyzing human intelligence based on fingerprints and brain dominance. STIFIn has five intelligence components: Sensing, Testing, Intuiting, Feeling, and Instinct. STIFIn is used to understand one's potential, the STIFIn method can help a person choose a more appropriate learning style, career, and self-development. In practice, the STIFIn method has implications according to the Islamic concept, namely Human Fitrah (QS. Ar-Rum: 30), the uniqueness of human beings (QS. Al-Hujurat: 13), and Psychology in Islam.